2007
DOI: 10.1002/ejic.200600819
|View full text |Cite
|
Sign up to set email alerts
|

Structural Distortion and Magnetic Behavior in Cyanide‐Bridged FeIII2NiII2 Complexes

Abstract: 6 pagesInternational audienceThe X-ray structure, spectroscopic, and magnetic properties ofacyanide-bridgedcomplex,{[(Tp*)FeIII(CN)3]2[NiII(bipy)2]2- [OTf]2}*2H2O (2) are described [Tp* = hydridotris(3,5-dimethylpyrazol-1-yl)borate; bipy = 2,2'-bipyridine; OTf = trifluromethanesulfonate]. Magnetic measurements indicate that 2 exhibits an S = 3 ground state and slow relaxation of the magnetization....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…24), with free perchlorate counter anions. Despite its large structural distortion, the size of the Fe 2 Ni 2 square unit is in agreement with those of cyano-bridged Fe 2 Ni 2 square clusters reported previously [29,[53][54][55][56]. The 1D chains are further linked through hydrogen bonds between perchlorate anions and (1S,2S)-chxn ligands.…”
Section: One-dimensional Assembliessupporting
confidence: 82%
“…24), with free perchlorate counter anions. Despite its large structural distortion, the size of the Fe 2 Ni 2 square unit is in agreement with those of cyano-bridged Fe 2 Ni 2 square clusters reported previously [29,[53][54][55][56]. The 1D chains are further linked through hydrogen bonds between perchlorate anions and (1S,2S)-chxn ligands.…”
Section: One-dimensional Assembliessupporting
confidence: 82%
“…All measurements began at 1.8 K and the temperatures were increased. The fresh sample (open circle) showed rapidly increasing c m T values from 1.8 to 11.6 K, followed by a gradual increase to the c m T value of 21.34 emu mol À1 K at 300 K; the value at 300 K is close to the Curie constant (20.34 emu mol À1 K) obtained by summing the uncorrelated spins of eight LS-Fe III (S = 1/2) and six Co II ions (S = 3/2) with the g Fe = 2.7 and g Co = 2.3, [2d, 3b] corresponding with the cluster in the [(LS-Fe 6 ] state. The magnetic susceptibility data suggested that antiferromagnetic interactions between the Fe III and Co II ions were operative and the notable change of the c m T values in the low and intermediate temperature ranges might be due to the orbital contribution from the metal ions.…”
Section: Wwwchemeurjorgmentioning
confidence: 92%
“…It is, therefore, assumed that three electrons were transferred from the [(LS-Fe 6 ] states upon the temperature increase. Note that no hysteresis was observed for desolvated 2.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
See 2 more Smart Citations